PENINGKATAN USAHA TERNAK KAMBING DI KELOMPOK TANI SUMBER SARI DALAM ANALISIS EKONOMI PENDAPATAN - S. Rusdiana; Rijanto Hutasoit (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2014)
This research was conducted at the District High King shavings District of North Sumatra Province. The purpose of the study was to determine the increase in goat  farming  goat  farmer  groups  in  the  analysis  of  pollen  sources  of  income.  The study was conducted in the village of Sumber High King and High King of Hope in District  District  shavings,  each  study  site  has  the  same  agro-ecosystems.  The  study was conducted by the method by filling  in a questionnaire survey using kuwesioner and  structured  interviews  with  15  respondents  farmers  and  15  farmer  groups koopertor  non-cooperators,  in  November-December  2012,  according  to  the information  from  the  Department  of  Agricultural  Extension  and  local  farming population  criteria  goats  and  primary  data  secondary  data  collected  was  analyzed using descriptive tabulation and analysis of the economy.The results of the research effort goat raising net income amounted Rp.8.411.168 Koopertor, 83/tahun, B/C ratio of 1.4, and goat enterprises are non Cooperators sebsar Rp. 1,644,051.24/year, B/C ratio of 1.2. This can increase the income of farmers in maintaining the well-being of families and the need for the application of technological innovations introduced  so that a more commercial farming goats and goats can be sustained presence in times to come.